FORMS OF ORGANIZATION OF RESEARCH ACTIVITY OF STUDENTS OF THE EDUCATIONAL BRANCH "TECHNOLOGY" - Rohozina, O.V. (Pedagogy of Higher and Secondary Education, 2008)
System of organization of Research activity of Future labour Training The main types of student’s research activity are described by author in this article. The main form and periods of forming student’s research skills are given.